Wild flora from central Andes of Peru: study of the Quilcas zone, Junín - Yarupaitán, Genaro (2003)
This work is a taxonomic study of the wild flora from Quilcas, Junin, in the central Andes of Peru. There are reported 214 species of plants in 140 genera and 52 families. Highest diversity is on Asteraceae with 55 species, and Poaceae with 22 species. There were reported 32 species as new for Junin. Floristic affinity analysis us may conclude similarity of Quilca with others regions of Peruvian Andes.